Limitations of Machine Translation - Shmavonyan, Gayane (Armenian Folia Anglistika, 2010)
Along with technological advancements worldwide there is a growing demand in machine translation as well. With its various and most diverse translation opportunities, computer translation, however, has its disadvantages and restrictions. At the current stage of technological development, translation done by a translator will provide a higher quality and effectiveness if it is combined with the employment of machine translation tools.